Histopathology of nile Tilapia oreochromis niloticus liver and kidney after long-term low level exposure to distilled liquors 30 degree - Sirinnapa Pumchae (Chulalongkorn University, 2007)
Thesis (M.Sc.)--Chulalongkorn University, 2004